2019
DOI: 10.1002/jemt.23157
|View full text |Cite
|
Sign up to set email alerts
|

Foliar epidermal anatomy of Lamiaceae with special emphasis on their trichomes diversity using scanning electron microscopy

Abstract: Foliar epidermal features were based on the micromorphology of trichomes types, epidermal cells and stomatal complex. Even though each feature has its own limited taxonomic value but collectively these characteristics may be systematically important especially for the discrimination and identification of complex and problematic taxa. The systematics significance of nonglandular (NGTs) and glandular trichomes (GTs), stomatal complex and epidermal cells of Lamiaceous flora were analyzed by using the light micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 45 publications
7
60
0
Order By: Relevance
“…The light microscopic analysis was performed for the investigation of foliar epidermal features. For LM both fresh and dried leaves were prepared using the technique of Gul et al (2018) with a little modification. The fresh leaves of collected samples were placed in water for about 2 hr to prevent them from drying.…”
Section: Light Microscopic Analysis For Investigation Of Foliar Epimentioning
confidence: 99%
See 2 more Smart Citations
“…The light microscopic analysis was performed for the investigation of foliar epidermal features. For LM both fresh and dried leaves were prepared using the technique of Gul et al (2018) with a little modification. The fresh leaves of collected samples were placed in water for about 2 hr to prevent them from drying.…”
Section: Light Microscopic Analysis For Investigation Of Foliar Epimentioning
confidence: 99%
“…Leaves of monocotyledonous taxa are mostly linear and have parallel venation although some taxa have broad leaves. Hence, foliar epidermal characters that is, trichomes and stomata have been used a taxonomic tool at various taxonomic ranks (Edeoga & Osawe, ; Gul et al, ). The foliar epidermal anatomy provides the taxonomic information of monocotyledonous taxa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Hemcinschi et al, (Hemcinschi, Gales, Stanescu, & Toma, ) observed the anamocytic‐type stomata as well. Foliar epidermal traits of the Ajuga bracteosa and Ajuga parviflora in Pakistan were found significant in the correct identification and delimitation of the related species (Gul et al, ). Foliar epidermal features were found useful to elucidate the systematics of the Lamiaceae species (Gul et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Ajuga reptans has a total of nine vascular bundles, one big in the center and four at each corner (Akçin, Özyurt, & Şenel, ). The genus Ajuga belongs to family Lamiaceae and is represented in Pakistan by only two species (Gul et al, ; Perveen & Qaiser, ); till to date no third species were added to this genus in the flora of Pakistan and with the addition of Ajuga reptance the number of species will be three.…”
Section: Introductionmentioning
confidence: 99%